Pendampingan Pembuatan Sistem Informasi dan Dokumentasi Berbasis Website Untuk Pelestarian Budaya Lokal Desa Songak - Jumawal; Aris Sudianto; Aida, Saadatul; Selindiani, Silda (Universitas Hamzanwadi, 2025)
With the development of information and communication technology (ICT), the use of the internet has become crucial in the preservation of local culture. Songak Village, located in Sakra District, East Lombok Regency, has cultural potential including history, customs, and local arts that need to be documented and promoted. However, the limited information systems and cultural promotion have led to a lack of attention from the younger generation towards cultural heritage. To address this, a website-based information system named